Historitas Studi Islam - Ahmad Firdaus; Jahida Azzahra; Risnawati Risnawati (Tasamuh: Jurnal Studi Islam, 2022)
Islam is a religion that has complex dimensions. It can be seen and understood from various points of view, phenomena, and also scientific disciplines. The study of Islam is not only related to issues of divinity or faith, but also includes the history of Islamic culture. If Islam is viewed from a normative perspective, Islam is a religion that can apply to the analytical and critical scientific paradigm. Meanwhile, if viewed from a historical perspective, Islam can be said to be a scientific discipline, because it is practiced by humans and grows and develops in human life, so that it can be called an Islamic science, where the scope of the discussion also looks at the social system and cultural phenomena. The purpose of this study is to find out and explain the meaning of the history of Islamic studies and the relationship between normativity and the history of Islamic studies. The research method is categorized in the type of library or literature study research, whether in the form of books, journals, and previous studies. So history or history is a science in which various events are discussed by taking into account the elements of place, time, object, background, and the actors of the event. Thus, normative and historical are closely related and cannot be separated because normative contains issues of divinity while historical contains historical values originating from the Qur'an and hadith.